Use of X-Ray Fluorescence Microscopy for Studies on Research Models of Hepatocellular Carcinoma - Paunesku, Tatjana; Gordon, Andrew C.; White, Sarah; Harris, Kathleen; Antipova, Olga; Maxey, Evan; Vogt, Stefan; Smith, Anthony; Daddario, Luiza; Procissi, Daniele; Larson, Andrew; Woloschak, Gayle E. (Frontiers in Public Health, 2021)
Introduction: TheraSphere® microspheres containing yttrium 90Y are among many radioembolization agents used clinically to reduce liver tumor burden, and their effects on cancer volume reduction are well-established. At the same time, concerns about off target tissue injury often limit their use. Deeper investigation into tissue distribution and long-term impact of these microspheres could inform us about additional ways to use them in practice. Methods: Healthy rat liver and rabbit liver tumor samples from animals treated with TheraSpheres were sectioned and their elemental maps were generated by X-ray fluorescence microscopy (XFM) at the Advanced Photon Source (APS) synchrotron at Argonne National Laboratory (ANL). Results: Elemental imaging allowed us to identify the presence and distribution of TheraSpheres in animal tissues without the need for additional sample manipulation or staining. Ionizing radiation produced by 90Y radioactive contaminants present in these microspheres makes processing TheraSphere treated samples complex. Accumulation of microspheres in macrophages was observed. Conclusions: This is the first study that used XFM to evaluate the location of microspheres and radionuclides in animal liver and tumor samples introduced through radioembolization. XFM has shown promise in expanding our understanding of radioembolization and could be used for investigation of human patient samples in the future.